EFEK PERENDAMAN EKSTRAK Spirulina platensis SEBAGAI IMUNOSTIMULAN TERHADAP JUMLAH LEUKOSIT DAN HITUNG JENIS LEUKOSIT IKAN GURAME (Osphronemus goramy) YANG DIINFEKSI BAKTERI Aeromonas hydrophila - LITTA LASYA EMANINTA SITEPU, 061211133106 (2016)
The Purpose of this research was to find out the potency of the extract of Spirulina platensis as immunostimulant on the amount of leucocyte and numbered kind of leucocyte of gurame fish that infected by Aeromonas hydrophila bacteria. Twenty gurame fish wis weight of 20 grams and length of 9 – 10 cm randomly divided into 5 groups. P0(-) as negative control was not submerged by the extract of Spirulina platensis and was out infected of Aeromonas hydrophila bacteria. P0(+) as positive control was not submerged in extract of Spirulina platensis but infected by aeromonas hydrophila 106 cell/ml. The first submersion was done on the first day for three hours, and the second submersion was done on 7th day for three hours, and then after 24 hours infected by Aeromonas hydrophila 106cell/ml. The blood of fish were taken on 4th day after infected, to examine the blood using calculation room and blood smear. Data would be analyzed by using analysis of variant (ANOVA). If there were any significant different between the treatment, analysis continued by using computer software SPSS 18 for windows. The result of the research showed that the extract of Spiruliana platensis could increase the amount of leucocyte, neutrophil, and monocyte of gurame fish.